2023
DOI: 10.3847/1538-4357/ad08bd
|View full text |Cite
|
Sign up to set email alerts
|

Partial Eruption of Solar Filaments. I. Configuration and Formation of Double-decker Filaments

Yijun Hou,
Chuan Li,
Ting Li
et al.

Abstract: Partial eruptions of solar filaments are the typical representatives of solar eruptive behavior diversity. Here we investigate a typical filament partial eruption event and present integrated evidence for the configuration of the pre-eruption filament and its formation. The Chinese Hα Solar Explorer Hα observations reveal a structured Doppler velocity distribution within the pre-eruption filament, where distinct redshift only appeared in the eastern narrow part of the southern filament region and then disappea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Bonnin et al (2013) first retrieved the location and morphology of the filament main skeleton by the filament automated recognition method by Fuller et al (2005) and then applied a curvematching algorithm to determine whether the filaments in different frames are the same. Actually, filaments sometimes split into several fragments or partially erupted, which represent intricate and dynamic evolution (Liu et al 2012;Shen et al 2012;Hou et al 2023;Sun et al 2023). Tracking filaments by extracting and parameterizing certain morphological features is only effective for relatively large filaments and short time intervals.…”
Section: Filament Trackingmentioning
confidence: 99%
“…Bonnin et al (2013) first retrieved the location and morphology of the filament main skeleton by the filament automated recognition method by Fuller et al (2005) and then applied a curvematching algorithm to determine whether the filaments in different frames are the same. Actually, filaments sometimes split into several fragments or partially erupted, which represent intricate and dynamic evolution (Liu et al 2012;Shen et al 2012;Hou et al 2023;Sun et al 2023). Tracking filaments by extracting and parameterizing certain morphological features is only effective for relatively large filaments and short time intervals.…”
Section: Filament Trackingmentioning
confidence: 99%
“…For the magnetic structure of double-decker filaments, Liu et al (2012) proposed two possible force-free magnetic configurations: a double flux rope equilibrium and a single flux rope above a sheared arcade. Although the two possible magnetic configurations were analytically validated to be stable (Kliem et al 2014), their formation mechanisms still require further observational and theoretical investigations (Hou et al 2023). It has been suggested that a double-decker filament can be formed by injecting a new filament into a preexisting one from below (Liu et al 2012;Zhang et al 2014;Zhu & Alexander 2014).…”
Section: Introductionmentioning
confidence: 99%